G432(P) All in the mind: a mindfulness tool for trainees. (May 2019) - Radia, T; Dowling, N; Hewett, S; McLoughlin, S; Jacob, H; Alviani, C; Broughton, S; Kingdon, C
Abstract : Background: Burnout is a work-related hazard for those working in Healthcare. A systematic meta-analysis demonstrated junior doctors experiencing burnout are twice as likely to be involved in patient safety incidents, to deliver suboptimal care and to receive low satisfaction ratings from patients. This year, for the first time, the GMC has asked trainee doctors and trainers a series of questions about burnout. Initial results identified that nearly a quarter of doctors in training are burnt out because of their work. Further research identified trainees in their early career are particularly at risk. Mindfulness-based interventions have a potential role in decreasing stress and burnout. Aims: To offer digital access to Mindfulness meditation to new ST1 doctors joining paediatrics at induction. We wanted to encourage early emphasis on self-care and reduce stigma around mental wellbeing. Method: We purchased a 12 month subscription to a digital mindfulness online platform called Headspace®. We designed and shared a one page leaflet which included a code for free access to activate individual accounts. The leaflet was shared at the ST1 induction (prior to rotation commencing). We also delivered a 10 min session during the induction outlining benefits and usage of mindfulness to focus on self-care. Alongside this, we surveyed current ST2 trainees on their ST1 experience focusing on self-care, sleep and mindfulness. Results: A total of 104 trainees attended ST1 induction. They were all offered access to Headspace® accounts. To date, 63/104 (61%) ST1s have activated their accounts in the one month since launch. The most accessed area of the platform is the sleep package (44%). In addition, the ST2's reported 64% trainees had their sleep affected more than once a week during their ST1 rotation. Conclusion: We have demonstrated good uptake of a digital mindfulness online platform, Headspace®. Early data from the study (still ongoing) include the positive impact of a digital mindfulness medium on trainees' self-belief and awareness of the importance of relaxation. We plan to survey the trainees at the end of ST1 to identify the impact through their first year of rotation and consider expanding the scheme further.